Observations of flux rope − associated particle bursts with GEOTAIL in the distant tail - A. Belehaki; E. T. Sarris; G. Tsiropoula; R. W. McEntire; S. Kokubun; T. Yamamoto (Annales Geophysicae, 1997)
Geotail energetic particle, magnetic field data and plasma observations (EPIC, MGF and CPI experiments) have been examined for a number of energetic particle bursts in the distant tail (120Re<|XGSM|< 130 Re), associated with moving magnetic field structures, following substorm onsets. The features obtained from this data analysis are consistent with the distant magnetotail dynamics determined first by ISEE3 observations and explained in terms of the neutral line model. At the onset of the bursts, before plasma sheet entrance, energetic electrons appear as a field-aligned beam flowing in the tailward direction, followed by anisotropic ions. Within the flux rope region, suprathermal ions exhibit a convective anisotropy, which allows determination of the plasma flow velocity, assuming that the anisotropy arises from the Compton-Getting effect. The velocities thus determined in the plasma sheet are estimated to be 200–650 km/s, and compare favourably with the velocities derived from the CPI electron and proton experiment. The estimated length of magnetic field structures varies between 28 and 56 Re and depends on the strength of the westward electrojet intensification. Finally, the three structures reported here show clear magnetic field signatures of flux rope topology. The existence of a strong magnetic field aligned approximately along the Y-axis and centred on the north-to-south excursion of the field, and the bipolar signature in both By and/or Bz components, is consistent with the existence of closed field lines extending from Earth and wrapping around the core of the flux rope structure. Key words. Magnetospheric configuration and dynamics · Magnetotail